The Relationship Between Self Efficacy, Learning Styles to the Learning Activeness of Prospective Teachers - Aruna Ngesti Lestari; Supartinah; Sekar Purbarini Kawuryan (Universitas Pendidikan Ganesha, 2024)
Active learning is a basic element that must be fulfilled to support the success of the learning process. However, student learning activeness has not emerged and the level of student self-efficacy is low and learning styles are varied. This study aims to analyze the relationship between self-efficacy and learning styles on student learning activeness. The research method used is descriptive quantitative with a survey approach. The subjects in this study were social studies students in grades 4A and 4B, totaling 105 students. The data collection technique used is a questionnaire. While the data analysis technique uses the reliability test for normality test, T test, F test and hypothesis test. The results showed that there was a positive relationship between variables seen from the output on the T test and F test with a significance value of (2-tailed) 0.00 <0.05, so it can be concluded that there is a positive relationship between self-efficacy and learning style in student learning activity. Therefore, it is recommended that lecturers or teachers pay attention to each characteristic of each student, not only focusing on the material, but also on the active learning of each student, so that students can actively participate in learning and build enthusiasm and confidence in learning. In addition, it is necessary to have a learning support room that supports the learning style of each student, especially when studying in class.